PEMIKIRAN EKONOMI ILMUWAN MUSLIM KONTEMPORER MADZHAB MAINSTREAM 1 - M. Ariel Ramadhani; Arifal Anugerhana Putra; Rafiffi Ali Hanan Santosa; Muhammad Taufik Abadi; Muhammad Aris Syafi’i (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The contemporary Islamic economic thought within the mainstream 1 school has emerged as a crucial framework for the development of inclusive and sustainable Islamic economics. Scholars such as Muhammad Abdul Mannan, Nejatullah Siddiqi, Syed Nawab Heider Naqvi, and Monzer Kahf have made significant contributions by introducing novel ideas that address the pressing economic challenges faced globally. This study aims to critically analyze the fundamental concepts put forth by these contemporary Muslim scholars within the mainstream 1 school and examine their applicability and significance within the global economic context.